Pengelolaan Penanaman Karakter Dalam Pembelajaran Biologi Di SMA Muhammadiyah 2 Gemolong Sragen - LUYANINGSIH, Sri; , Dr. Suyatmini, M.Si; , Dr. Sumardi, M.Si (2015)
This research aims to describe the character cultivation in Biology learning in the classroom, in the laboratory, and outside the classroom (natural) at Senior High School of Muhammadiyah 2 Gemolong Sragen. This research is qualitative research with ethnographic research design. Implementation of research in Senior High School of Muhammadiyah 2 Gemolong Sragen. Data was collected by interview, observation and document. Data analysis technique using an interactive model of analysis. These results indicate that character cultivation management in biology learning in the classroom, in the laboratory, and outside the classroom (natural), conducted by preparing plans in the form of lesson plan by inserting cultivation of moral values, organizing learning schedule, implement at every opportunity to interact with students, and supervising through the achievement and attitudes. Moral values are submitted by teachers to students, namely honest, hard working, tolerance, curiosity, communicative, recognize excellence, responsibility, caring environment.